Observed Landscape Responsiveness to Climate Forcing. Issue 1 (18th January 2022) - Feldman, Andrew F.; Short Gianotti, Daniel J.; Trigo, Isabel F.; Salvucci, Guido D.; Entekhabi, Dara
Abstract: Climate variability and change shift environmental conditions on global land surfaces, creating uncertainties in predicting hydrologic flows, crop yields, and land carbon uptake. Land surfaces can present varying degrees of inertia to atmospheric forcing variability (e.g., precipitation). This study asks: are regions with the most variable environmental forcing necessarily the regions with the largest land surface variability? Specifically, it seeks to determine why land surfaces show varying responsiveness to environmental forcing. The degree to which and the mechanisms for how landscapes modulate the forcing are evaluated using a decade‐long satellite observation record of Africa's diverse climates. Surface responsiveness is quantified using intra‐seasonal energy flux variability, based on the observed diurnal temperature amplitude. We map the responsiveness and analyze the underlying mechanisms over intra‐seasonal timescales (especially interstorms). We show that, at a location, land surface responsiveness is dependent on the soil moisture distribution and the nonlinear relationship between energy fluxes and soil moisture. Land surfaces with greater responsiveness to climate are those with soil moisture distributions that span the threshold between evaporation regimes and spend most of their time in the water‐limited regime. Consequently, surface responsiveness mechanisms drive land surface variability beyond high climatic variability. Since we find these results to hold from intra‐seasonal to interannual timescales, we expect that these responsive regions will be most vulnerable to long‐term shifts in climate forcing. The quantification of these phenomena and determination of their geographic distributions based on observations can help assess land surface models used to evaluate hydrologic consequences of climate change. Plain Language Summary: Variations in rainfall and incoming sunlight amount shift land surface conditions (i.e., evaporation) and constrain our ability to predict crop yields and carbon sequestration. Nevertheless, some landscapes respond more to rainfall and sunlight variability than others. Using recent decade‐long satellite observations of surface temperature and soil moisture across Africa, we investigate whether regions with the most rainfall and sunlight variability are also those with the largest land surface variability and why. Indeed, we find that more rainfall and sunlight variability do increase the land evaporation and temperature variability. However, regions that spend time in the water‐limited evaporative regime (a drier soil state where soil moisture influences evaporation rates) have an amplified land surface response to atmospheric variability. These regions tend to be semi‐arid, but isolated humid regions also show this behavior because the water‐limited regime is defined by factors beyond mean moisture availability. While these mechanistic findings are based on daily‐to‐weekly land and atmospheric variability, we find these results also hold on longer timescales of year‐to‐year variations. As a result, these regions spending time mainly in the water‐limited regime likely have increased vulnerability to climatic changes in rainfall and sunlight amount. Key Points: Observed intraseasonal energy flux variance (from diurnal temperature amplitude) is used to quantify surface responsiveness to forcings Intraseasonal mechanisms based on the energy flux‐soil moisture relationship and weather variability describe responsiveness patterns Spending more time in the water‐limited evaporative regime enhances surface responsiveness across intraseasonal to interannual timescales